PENGARUH KEPERCAYAAN DAN HARGA TERHADAP KEPUASAN PENGGUNA JASA TRANSPORTASI ONLINE MAXIM - Olivia Laura Sahertian; Stevanus Johan Gomies; Salmini Salenussa (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This research aims to determinethe influence of trust and price on User Satisfaction of Maxim’s online transportation services. This study uses a quantitative approach . The population in this study were people who had used Maxim’s online transportation services in Suli Village, Salahutu District, Central Maluku Regency. The sampling technique used a purposive sampling method with a sample size of 50 people. The data collection technique uses a questionnaire whose validity and reliability have been tested, and the data analysis technique used is multiple regression. The research results show that : the trust has a positive and significant effect on satisfaction with using Maxim’s online transportation services; price has a positive and significant effect on satisfaction with using Maxim’s online transportation services; trust and price simultaneously have a positive and significant effect on user satisfaction.